Сan't you see? It's a Cupid's bow basal cell carcinoma! - Georgi Tchernev; Simona Kordeva; Ilia Batashki; Atanas Batashki; Ilia Lozev (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Epithelial tumors, and in particular basal cell carcinoma (BCC), extremely rarely affect the area known as Cupid's bow, and their treatment remains a serious challenge. We present a 53-year-old patient with a history of painful sunburns in the past and BCC of the neck, successfully treated surgically. The reason for the hospitalization was the appearance of a new nodular achromic lesion in the area of ˝Cupid's bow˝ (upper lip), which preoperatively was verified histopathologically as BCC. Elliptical excision under local anesthesia was performed, and the resulting defect was closed using an undermining surgical approach, followed by single skin sutures. The patient's 4-month follow-up was uneventful with no evidence of recurrence. Treatment options for BCCs in the area of Cupid's bow and the advantages of elliptical excision in the area are discussed.